2017
DOI: 10.4103/1357-6283.210501
|View full text |Cite
|
Sign up to set email alerts
|

Medical ethics education in China: Lessons from three schools

Abstract: We conclude that the development of medical ethics education in China is promising while much improvement is needed. In addition, ethics education is not confined to the walls of medical schools; the society at large can have significant influence on the formation of students' professional values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 3 publications
2
18
0
Order By: Relevance
“…Successful curriculum development implementation requires continuous and multifaceted consideration. There is a four-stage framework describing the action plan for progressive changes in the curriculum development, specific to bioethics curriculum in medical education over time, in terms of the implementation, content, teaching capacity, and instruction method (Sherer et al 2017 ). In Stage 1, there is no bioethics course in the institution.…”
Section: Introductionmentioning
confidence: 99%
“…Successful curriculum development implementation requires continuous and multifaceted consideration. There is a four-stage framework describing the action plan for progressive changes in the curriculum development, specific to bioethics curriculum in medical education over time, in terms of the implementation, content, teaching capacity, and instruction method (Sherer et al 2017 ). In Stage 1, there is no bioethics course in the institution.…”
Section: Introductionmentioning
confidence: 99%
“…There is no consensus as to which is the most effective teaching and assessment method in bioethics education, and lecture emerged as the most commonly practised by medical schools in the East 9 and the West. 24 Considering the crowded timetable in the medical curriculum and limited expertise to teach bioethics, using didactic lecture is acceptable to alleviate packed schedule and deliver quality teaching.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…8 In China, most medical schools provide bioethics courses intermittently with varying teaching hours and placed different emphasis on teaching topics. 9 In India, bioethics is delivered sporadically during the entire medical curriculum or remained unimplemented in some medical schools. 10 In Southeast Asia region, other countries such as Pakistan, 11 India, 12 and Indonesia, 13 only a handful of institutions impart bioethics in the medical education, whereas some are not yet prepared to commit to bioethics teaching in the curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…In the UK one study reported that only 45% of schools taught ethics and as a separate topic with the majority reporting that it is taught in classrooms (Brooks & Bell 2017). The majority of teachers of medical ethics in China have backgrounds in humanities or social sciences rather than in medicine and there is a tendency to teaching the theories and principles of ethics whilst not relating them to clinical practice ethical dilemmas (Sherer et al 2017).…”
Section: Description Of a New Education Methods Or Toolmentioning
confidence: 99%
“…It has only been in the last 30 years that teaching medical ethics has been formally included within the medical curriculum following the Pond Report (1987) and the publication of Tomorrow's Doctors (1993). It is now recognized as important and central in undergraduate medical curricula (Sherer et al 2017;General Medical Council 1993;Miles et al 1989, Institute of Medical Ethics 1987. The purpose of integrating medical ethics into the medical curriculum is to provide opportunities for understanding and analysing ethical dilemmas, and guide doctors in making thoughtful ethical clinical decisions (Beigy et al 2016).…”
Section: Introductionmentioning
confidence: 99%